Misrepresenting religious education's past and present in looking forward: gearon using Kuhn's concepts of paradigm, paradigm shift and incommensurability - Jackson, Bob (Journal of beliefs and values, 2015)
In looking to the future, some writers on religious education (RE) have attempted to evaluate current approaches to the subject. Some have characterised any significant change in approach as a "paradigm shift", a term derived from Thomas Kuhn's work in the philosophy of science. This article examines the uses of the terms "paradigm", "paradigm shift" and "incommensurability" in Liam Gearon's book MasterClass in Religious Education. I argue that Gearon misapplies Kuhn's concepts, that his own account of paradigms of RE is internally inconsistent, and that his discussion - partly through placing the views of others within a rigid framework of constructed paradigms - contains some misrepresentations of their work. The critique is pertinent to the debate about the nature and future of RE for, if evaluations of present and past models of RE are defective, their use in re-thinking the shape and content of the subject is highly questionable.